AN INVESTIGATION INTO STYLISTIC DEVICES COMMONLY USED IN RIDDLES: ENGLISH vs VIETNAMESE - Ph.D NGUYỄN TẤN THI (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
- To understand more about the way English and Vietnamese riddles are created, and how they work in each culture. - To help teachers deal with a rather straightforward use of riddles for free -practice and other activities in teaching English.